Diplophyllum purpurascens (Scapaniaceae, Marchantiophyta)—a new species from Sino-Himalaya (China) - Bakalin, Vadim; Vilnet, Anna; Klimova, Ksenia; Ma, Wen Zhang; Nguyen, van Sinh (Phytotaxa, 2020)
Diplophyllum purpurascens is described from the northern part of Yunnan Province in China based on the evidence obtained during an integrative study. The new species differs from congeners in its pinkish to purplish gemmae—a feature not known before in Diplophyllum. The species occupies a basal position in a clade composed of D. sibiricum, D. obtusifolium and D. andrewsii and is morphologically similar to all the aforementioned species. Diplophyllum purpurascens probably belongs to the group of Sino-Himalayan liverworts—a very diverse, little understood complex of taxa.